Evidence of physical violence and torture in refugees and migrants seeking asylum in France. (January 2021) - Deps, Patrícia; Collin, Simon M.; Aborghetti, Hugo Pessotti; Charlier, Philippe
Abstract: Objectives: The increasing numbers of migrants and refugees to Europe include persons seeking asylum, many of whom will have experienced physical violence and torture. Here we describe the personal histories and clinical evidence of violence and torture among attendees at a public health specialist service in France. Methods: Physicians in a multidisciplinary team conducted examinations to corroborate refugees' skin lesions and other signs of injury with self-reported histories of physical violence and torture to provide evidence for asylum applications. Results: The 240 asylum seekers assessed between October 2016 and September 2018 were mostly male (89% (213/240)) with median age 29 years (IQR 26–34 years) and originating from north and west Africa. Consultations took place on average 15 months after arrival in France. In most cases (58%) the reason for seeking asylum was political persecution. Almost all attendees (94%) presented with scars. The most common mechanisms of injury were beatings (84%), burns (32%) and cuts/stab wounds (15%). Sexual violence was reported for 37% of women (10/27) and 4% of men (9/213). Police tended to use multiple methods for inflicting injuries, whereas the army and non-state actors mostly inflicted beatings. Sexual violation was most commonly reported for violence inflicted by family members or partners. Corroboration of lesions with patients' histories of physical violence and torture was affirmative in 93% (224/240) of cases. Conclusion: For this ethnically diverse group, a specialist service which can provide clinical corroboration of self-reported histories of physical violence and torture to support asylum applications is an essential minimum. Highlights: A diverse group of asylum seekers in France presented with shared characteristics. In almost all cases (>90%), clinical corroboration with histories was affirmative. Health provision in Europe needs to include specialist services for asylum seekers.